(untitled) (Global Journal of Management and Business Research, 2021)
Empirical evidence on the association between overhead costs and non-volume related cost drivers is mixed. Anderson and Sedatole (2013) offer possible explanations for the lack of evidence and find that the cost hierarchy is descriptive of the association between resource consumption and production activity. In this paper, we provide evidence on the presence of the cost hierarchy by studying the behavior of indirect production labor costs using daily data for five years from seven production departments of an industrial equipment manufacturer.